2021
DOI: 10.1111/medu.14437
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal, narrative study of professional socialisation among health students

Abstract: Purpose Interprofessional collaboration (IPC) among health professionals is well‐recognised to enhance care delivery and patient outcomes. Emerging evidence suggests that the early socialisation of students in health professional programmes to teamwork may have a positive impact on their future as collaborative practitioners. With a purpose of contributing to growing evidence on the processes of professional identity construction, and to explore how early expectations and perceptions of IPC develop during prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Of note, given all graduates in this study had prior interprofessional education as students, findings from this study support the inclusion of an interprofessional curricula with an explicit focus on facilitating students' interprofessional identity development. This recommendation echoes recommendations in previous studies exploring students' development of interprofessional identity [27,51,52]. A desired outcome is for new graduates to enter the health workforce with a clear understanding of, and commitment to, work interprofessionally in a range of service delivery contexts.…”
Section: Discussionsupporting
confidence: 60%
“…Of note, given all graduates in this study had prior interprofessional education as students, findings from this study support the inclusion of an interprofessional curricula with an explicit focus on facilitating students' interprofessional identity development. This recommendation echoes recommendations in previous studies exploring students' development of interprofessional identity [27,51,52]. A desired outcome is for new graduates to enter the health workforce with a clear understanding of, and commitment to, work interprofessionally in a range of service delivery contexts.…”
Section: Discussionsupporting
confidence: 60%
“…One of the important outcomes of IPE is the socialisation of professions to each other (Bloomfield et al, 2021). The early socialisation of students to teamwork in health professional programmes is understood as having a positive contribution to collaboration within the workplace and the development of an interprofessional identity (Price et al, 2021). The students in this study were given the opportunity to ask anonymised questions of their professional colleagues during an initial socialisation experience that occurred prior to a planned interprofessional intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare organisations and healthcare education systems need to recognise the potential impact of this on collaboration and teamwork (McKethan & Brammer, 2010;Weller et al, 2014). This reinforces the importance of these organisations working together to facilitate the development of an interprofessional identity with early socialisation amongst healthcare students (Price et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have repeatedly demonstrated that students often have a superficial understanding of their chosen careers at the beginning of their pre‐licensure education. Moreover, their narratives of professional socialisation are largely void of any reference to teamwork and collaboration 3 . This is an especially troubling finding given that effective teamwork and interprofessional collaboration are shown to improve system and patient outcomes 4 .…”
mentioning
confidence: 99%
“…In an attempt to understand how health professional students develop an interprofessional identity, we have conducted several qualitative studies exploring the socialisation experiences that inform students’ understanding of their roles as collaborative team members, including the informal socialisation that happens as early as career choice decision‐making 3 . We have discovered that images and messages of teamwork in health professional recruitment materials, including university websites, are largely absent.…”
mentioning
confidence: 99%